Effectiveness of Screw Surface Coating on the Stability of Zirconia Abutments After Cyclic Loading - Basilio, Mariana de Almeida [UNESP]; Butignon, Luis Eduardo [UNESP]; Arioli Filho, João Neudenir [UNESP] (Quintessence Publishing Co Inc, 2012)
Purpose: Different surface treatments have been developed in attempts to prevent the loosening of abutment screws. The aim of the current study was to compare the effectiveness of titanium alloy screws with tungsten-doped diamond-like carbon (W-DLC) coating and uncoated screws in providing stability to zirconia (ZrO2) ceramic abutments after cyclic loading. Materials and Methods: Twenty prefabricated ZrO2 ceramic abutments on their respective external-hex implants were divided into two groups of equal size according to the type of screw used: uncoated titanium alloy screw (Ti) or titanium alloy screw with W-DLC coating (W-DLC/Ti). The removal torque value (preload) of the abutment screw was measured before and after loading. Cyclic loading between 11 and 211 N was applied at an angle of 30 degrees to the long axis of the implants at a frequency of 15 Hz. A target of 0.5 x 10(6) cycles was defined. Group means were calculated and compared using analysis of variance and the F test (alpha=.05). Results: Before cyclic loading, the preload for Ti screws was significantly higher than that for W-DLC/Ti screws (P=.021). After cyclic loading, there was no significant difference between them (P=.499). Conclusions: Under the studied conditions, it can be concluded that, after cyclic loading, both abutment screws presented a significant reduction in the mean retained preload and similar effectiveness in maintaining preload. INT J ORAL MAXILLOFAC IMPLANTS 2012;27:1061-1067
Keywords: abutment screws; cyclic loading; implant preload; screw coating surface; zirconia abutment